Predictors of laptop use in teaching and learning among secondary school mathematics and science teachers - Moses, Priscilla (2012)
With the growing emphasis on technology, Mathematics and Science teachers were provided with laptops as an instructional tool to improve their lesson delivery. The focus of this study was to investigate the factors that influence the use of laptops in the teaching and learning among the secondary school Mathematics and Science teachers. The predictor factors were laptop competence, perceived ease of use, perceived usefulness, attitude towards laptop use, administrator’s support, and technical support. This study was based on a quantitative descriptive research using a set of questionnaire. The validity of the instrument was established through a panel of experts. Pilot test was carried out among 38 teachers and the Cronbach’s alpha coefficient value was found to range from .731 to .978. The respondents of this investigation were secondary school Mathematics and Science teachers from the Central Region of Malaysia. The total sample of Mathematics and Science teachers was 473. Descriptive statistics and Structural Equation Modeling using SPSS and AMOS was employed in this study. Several significant findings emerged from this study. The results attained from the analysis generated a model — the Malaysian Teachers’ Laptop Use Model (MyTeLUM) that could be used to predict the use of laptops among the Mathematics and Science teachers for teaching and learning. The significantly emerged paths were: 1) laptop competence influenced perceived usefulness (B= .184, p < 0.05); 2) perceived ease of use influenced perceived usefulness (B = .451, p < 0.001); 3) perceived usefulness influenced attitude (B = .691, p < 0.001);4) perceived usefulness influenced laptop use (B = .256, p < 0.001); 5) attitude influenced laptop use (B = .481, p < 0.001); 6) technical support influenced perceived ease of use (B = .193, p < 0.001); and 7) technical support influenced perceived usefulness (B = .119, p < 0.05). However, only administrator’s support (B = 0.022, p > 0.05) was found to be insignificant in predicting the use of laptops among the teachers. In addition, two new additional paths that were statistically significant were also identified from the MyTeLUM. The first path showed that laptop competence predicted perceived ease of use (B = .623, p <0.001) and the second path that emerged showed that technical support influenced laptop competence (B = .199, p < 0.001). Meanwhile, the four mediating variables identified in this study were perceived ease of use, perceived usefulness, attitude towards laptop use, and laptop competence. Three of the intervening variables acted as partial mediators, except for the perceived usefulness which played the role of a total mediator between the variables. Furthermore, the MyTeLUM yielded dissimilar results on the influence of the variables for Mathematics (technical support on perceived usefulness;B = .128, p > 0.05) and Science (laptop competence on perceived usefulness;B = .000, p > 0.05) subjects. Out of the six predictors, five were found to be significant in influencing the use of laptop either directly (perceived usefulness and attitude towards laptop use) or indirectly (laptop competence, perceived ease of use, and technical support). Consequently, nearly half of the variance (46.7%) in laptop use was explained by the five variables for the teaching and learning. This study proposes that greater emphasis should be placed on the teachers’ attitude towards laptop use and perceived usefulness in educating, preparing, and training the teachers to utilise the laptops for teaching and learning. Hence, the findings of this research may benefit and provide productive directions especially to the Malaysian Ministry of Education as a laptop initiative policy maker in order to make the investment yield more effective results.